High Impedance Protection Applications for Tripping Acceleration in Networks with DG - Jäger, Johann; et al. (2005 IEEE/PES Transmission and Distribution Conference & Exhibition: Asia and Pacific, 2005)
The presented paper is dealing with protection principles which are preferable applied to networks with distributed generation (DG). A basic physical explanation of the high-impedance protection principle in relation to the low-impedance principle will be given considering the transient behaviour in particular. It can be shown that special requirements on the protection co-ordination for networks with DG can be covered by the high-impedance protection principle. Measurement results of a high current lab confirm the favourable behaviour of the high-impedance protection principle. It was also possible to investigate the transient behaviour of the high-impedance principle under extreme conditions like CT remanence effects. A close correlation between digital simulation and measurement results of the transient behaviour could be achieved during the investigations. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.leen.highim
Keywords: Digital simulations; Distributed generation; High-impedance protection; Measurements; Transient behaviour